APLICABILIDADE DE INDICADORES DE DESENVOLVIMENTO SUSTENTÁVEL NORMATIZADOS ESTUDO DE CASO DO PROGRAMA MUNICÍPIO VERDE AZUL 2017 - Sena, Filipe; Abiko, Alex (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Sustainable development presents a number of challenges of applicability for the real alignment with local interests, as well as difficulties in defining which themes are a priority and should be added to the progress agenda. In the international sphere, the complexity of the theme is being addressed by ISO with the creation of a family of standards for sustainable communities, which, by its general characteristics, should be adopted and tested in various environments on the planet. In Brazil, the publication in 2017 of the standard ABNT NBR ISO 37120 - "Desenvolvimento sustentável em comunidades - Indicadores para serviços e qualidade de vida" - was the first adoption of the ISO 37000 family of standards on the subject. Later in 2017, this standard was also applied for the first time in the ambit of the program "programa município verde azul" of the environmental secretary of the state of são paulo. The results show that, although municipalities have the capacity to use the standard, using their own or broad state databases, it is necessary to verify the quality of the data obtained and, mainly, the capacity of analysis, process and use of this data in the construction of local actions.